MON-432 Symptomatic Pituitary Metastases: A Report of 16 Cases - Loto, Monica (J Endocr Soc, 2019)
Introduction: Pituitary Metastases (MTS) are infrequently seen in clinical practice. The incidence ranges from 0.14 to 28%. Breast and lung cancer are the primary sites that most frequently metastasize to sellar region, between the sixth and seventh decades of life. Most cases are diagnosed in patients with advanced malignant disease, however, in 20-30%, symptoms of pituitary involvement can precede the diagnosis of the primary tumor. Objectives: To evaluate symptoms at presentation, hormonal, radiological and histological findings, management and outcome of a series of patients with pituitary MTS. Patients and methods: medical records of 16 patients from eight Endocrine Centers were reviewed. Ten patients had histological confirmation of the pituitary MTS, 6 were not operated, being the diagnostic criteria the presence of sellar mass associated with diabetes insipidus (DI) and / or sudden-onset of neuro-ophthalmological symptoms in patients with confirmed primary neoplasia. Results: The median age was 54 years (range 35-70), 9 women (56.2%). The sites of the primary tumor were: 7 lung (44%), 5 breast (32%), 1 follicular thyroid carcinoma (6%), 1 Hodgkin lymphoma (6%), 1 poorly differentiated carcinoma (6%), and 1 clear cell renal carcinoma (6%). The median time between the diagnosis of the primary neoplasm and the occurrence of the pituitary MTS was 12 months (range: 3-120). In 9 patients (56.2%), the diagnosis of the primary neoplasm was made after the finding of the symptomatic sellar mass. DI was found in 14 patients (87.5%), adenohypophyseal deficit in 12 (75%), visual disorders in 10 (62.5 %), headache in 6 (37.5%) and cranial nerve deficits in 6 (37.5%). In 68.7% (11 patients), other MTS were detected. Fifteen patients were evaluated by MRI and one by CT: 13 (81.3%) harbored supra / parasellar masses, and the remaining 3 had lesions limited to the pituitary gland, with stalk thickening and lack of spontaneous neurohypophysis hyperintensity in 2 of them. In all cases diffuse gadolinium uptake was present. Fourteen patients died (87.5%), with a median survival time of 6,5 months (range: 1-36); the remaining 2 are still alive with a follow-up period of 4 and 12 months respectively. Conclusions: In this series of 16 patients with pituitary MTS, the most frequent primary neoplasms were lung and breast. Median age was lower than in published series. DI was the most common condition at presentation, followed by hypopituitarism and visual disorders. The short survival was related to the extent of the disease at the time of diagnosis. In more than half of the cases the diagnosis of primary neoplasia was made through the symptomatic pituitary mass. In the presence of a pituitary lesion with diffuse gadolinium uptake, associated with DI and / or acute visual deficit, pituitary MTS should be suspected even in patients without a history of oncological disease.